DISEÑO DE UN SISTEMA CONTABLE Y ANÁLISIS FINANCIERO EN EL CLUB LIGA DEPORTIVA UNIVERSITARIA DE LA CIUDAD DE LOJA, EN EL PERIODO ENERO – ABRIL DEL AÑO 2014 - García Jiménez, Lady Alexandra (2016)
The work of thesis named " DESIGN OF A COUNTABLE SYSTEM AND FINANCIAL ANALYSIS IN THE CLUB SPORTS UNIVERSITY LEAGUE OF LOJA's CITY, IN THE PERIOD ON JANUARY - APRIL, 2014 ", developed in agreement to the requirements of the Regulation of Academic Regime of Loja's National University, and previously to choose the Degree and Engineer's Title in Accounting and Audit, Public Book-keeper - Auditor. For the development of the work of thesis there decided in planned form each of his phases, being necessary for his correct execution, to use different methods that helped to the compilation of the necessary information, they facilitated the study of procedure, dispositions and theoretical modals that allowed to give fulfillment to the general aim to design a Countable System; likewise the specific raised aims were fulfilled satisfactorily, since there was elaborated a Plan and Manual of the Accounts that integrate the assets, liabilities, heritage, income and expenses of agreement to the needs of the club, using the system of decimal codification; there was effected the raising of the Initial Inventory of goods, rights and obligations in order to know his exact value for which designed a format where there consists code, quantity, detail, unitary value and total value, and one proceeded to realize a physical count, establishing that possesses an assets of $ 232.600,96, a liabilities of 6 $ 754.605,68 and a heritage of $ - 522.004,72, determining this way his State of Initial Situation; later it was necessary to elaborate auxiliary records of accounting, between them: You will help of Sales of Credits, Will help of Quota of Players, Will help of Fixed, Major Auxiliary Assets of Sale of goods and services, Major Auxiliary of Box, Major Auxiliary of Inventory of Supplies and Materials, auxiliary records of the Ticket offices of the different sports provoked meetings and Roles of Payment, that together with the documentation compiled source such as vouchers of sale, of retention and vouchers of payment, between others, they allowed the record of the transactions in the principal books of accounting, initiating with the Daily Book, which was effected by means of the application of the System of Multiple Account or Periodic Inventory, in this one there was registered also the respective adjustments of depreciation of fixed assets, provisions, consumptions and regulation of goods; later the mayorización was realized to determine the balances of the accounts that intervene in the countable process; the Trial balance and Leaf of Work was effected; up to managing to establish the State of Financial Situation determining that on April 30, 2014 the club possesses an assets of $ 349.238,39, a liabilities of $ 1.378.211,33 and for ende his heritage is of $-1.028.972,94, it is necessary to stress that the heritage of the club is composed in-0,12 % by the contributions of the partners and in 100,12 % by the Losses of Previous Exercises as well as also of the current one, situation that might be offset by means of the accomplishment of new 7 monetary contributions on the part of the partners by the aim to increase the heritage of the club and to possess a major economic support that serves to face to any contingency that one presents; of equal form there was elaborated the State of Economic Situation, establishing that obtained income of $ 520.330,54, expenses of $ 1.027.298,76, and for ende a loss of $-506.968,22; also the Effluence state of Cash was elaborated having a cash and equivalent of cash of $ 46.242,91 availably at the end of the period to continue with the normal operations of the club. Finally the process before described allowed to obtain reliable, opportune and veracious information, in base of which I effect a Financial Analysis applying the Vertical Analysis and indicators of liquidity and debt to examine the economic and financial situation of the club, of agreement to which the results were announced to the executives by means of the respective report, indicating that exists a deficient level of liquidity and high index of debt due to the high restriction of income, therefore it is suggested that corrective policies should be adopted focused to overcoming the negative results and serious crisis that appeases the organization, with the intention of assuring his survival and development, taking he arouses of that it is a question of an organization of supreme importance that it has represented satisfactorily to our country in the sports area in checks celebrated internationally.